ANALISIS YURIDIS TERHADAP PENYELESAIAN GUGATAN SEDERHANA DI WILAYAH HUKUM PENGADILAN NEGERI PEKANBARU - Zonia, Rizkiyah Putri; Bachtiar, Maryati; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Regulation of the Supreme Court (PERMA) No. 2 Year 2015 on Procedures for Settlement of Simple Claims, PERMA is referred to as the milestone of